Penerapan Balanced Scorecard Sebagai Pengukuran Kinerja Perusahaan (PT. Gde Kadek Brothers Layar Antarnusa-Bounty Cruises) - Rika Maharani, Ida Ayu; Budiasih, I.Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
This study aims to determine the performance of companies using Balanced Scorecard method that includes performance measurement from the perspective; finance, customers, internal business processes, and learning and growth. This study used a qualitative descriptive approach with data collection sourced from the primary data that is by conducting interviews and questionnaires and secondary data is by collecting data that already exist. The company's performance with Balanced Scorecard in the period of 2015 and 2016 resulted in overall good performance of the company. The results of this study support the performance theory that explains that performance can serve as a benchmark to determine the success of corporate strategy. The use of Balanced Scorecard method in measuring the performance of the company produces a picture of the company's performance financially and non-finance so that this performance measurement method can be applied in the company as a consideration of management to develop strategies that will be used to achieve the vision and mission of the company. Keywords: performance, performance measurement, balanced scorecard